THE CONTRIBUTION OF THE PROCEDURAL CONTRACTS FOR THE TRANSFORMATION OF THE LITIGATION CULTURE AND THE GENERAL PRINCIPLES OF INTERPRETATION AND CONTROL - Anderson de Paiva Gabriel (Revista Eletrônica de Direito Processual, 2018)
The purpose of this article is to analyze, under the premises of modern procedural science and the Federal Constitution of 1988 and the Code of Civil Procedure/2015, the institute of procedural contracts as one of the most evident results of the achievement of a model of process guided by cooperation and ethics, which can contribute to the development of new techniques and methods undertaken in the pacification of conflicts, leading to the transformation of the culture of litigation.